Life‐history characteristics of an exploited bonefish Albula glossodonta population in a remote South Pacific atoll. Issue 2 (27th June 2019) - Filous, Alexander; Lennox, Robert J.; Coleman, Richard R.; Friedlander, Alan M.; Clua, Eric E. G.; Danylchuk, Andy J.
Abstract: Bonefishes Albula spp. are important components of subsistence fisheries and lucrative sport fishing industries throughout their circumtropical distribution. In Oceania, however, Albula spp. have historically been overexploited and there is a growing need to balance the demands of competing fishing sectors, making the description of their life history a regional priority. To this aim, we collected biological samples from Albula spp. of Anaa atoll, French Polynesia, to identify the species that compose the stock and estimate their life‐history parameters including age, growth, reproduction and natural mortality. Our results indicate that Albula glossodonta is the species of bonefish present, with a maximum age that is below the, 20 year longevity of the genus (8 years in males and 10 years in females). Differential growth patterns existed between the two sexes ( L ∞ = 58, 78 cm fork length ( L F ) and K = 0.38, 0.21 for males and females, respectively). Males attained sexual maturity at 43 cm L F ( c . 3 years) whereas females matured at 48 cm L F ( c . 4 years) and oocyte production was significantly related to body mass, with a maximum batch fecundity of 1, 133, 767 oocytes in a 4406 g (70 cm L F ) female. The gonado‐somatic index of harvested fishes indicated that the spawning season extends from March through September. Based on the observation of a, 20 year bonefish at the proximate Tetiaroa Atoll and several empirical models, estimates of natural mortality ranged from 0.21 to 0.68; however, an estimate of 0.21 was deemed most appropriate. This information facilitated the resurgence of a Rahui (temporary fishing closure) and community‐based management to protect A. glossodonta during a critical portion of their spawning season and in this context our results provide an important demographic baseline in evaluating the recovery of this fishery.